Physical Exercise To Recovery of Consciousness in Post Operative Patients With General Anesthesia - Hapipah, Hapipah; Apsarina, Erida; Istianah, Istianah (STRADA : Jurnal Ilmiah Kesehatan, 2020)
General anesthesia is one of the techniques that is often chosen in performing surgery as a painkiller when going through surgery, followed by loss of consciousness. Early post-surgery there may be aspiration and decreased ventilation. This study aims to find out the effect of physical exercise to recovery of consciousness of post operative patients with general anesthesia. This study is Pre experimental with one shot case study design with 20 respondents. The technique used to collect samples is purposive sampling. Instruments in this study used Aldrete score. The data analysis showed an average difference in the aldrete score scoring of the control and the intervention group (4), (4), (6.1), (7.8), (8.3), (9.3) and (4), (6), (9.3), (9.9), (9.9), (10). The results of the data analysis showed a signification value of 0.000 ( < 0.05), which means there was a difference in consciousness recovery between the intervention group and control group